Identity, community and care in online accounts of hereditary colorectal cancer syndrome. Issue 2 (3rd April 2018) - Ross, Emily; Broer, Tineke; Kerr, Anne; Cunningham-Burley, Sarah
Abstract : Sociological literature has explored how shifts in the point at which individuals may be designated as diseased impact upon experiences of ill health. Research has shown that experiences of being genetically "at risk" are shaped by and shape familial relations, coping strategies, and new forms of biosociality. Less is known about how living with genetic risk is negotiated in the everyday and over time, and the wider forms of identity, communities and care this involves. This article explores these arrangements drawing on online bloggers' accounts of Familial Adenomatous Polyposis (FAP). We show how accounts of genetic risk co-exist with more palpable experiences of FAP in everyday life, notably the consequences of prophylactic surgeries. We consider how the act of blogging represents but also constitutes everyday experiences of hereditary cancer syndrome as simultaneously ordinary and exceptional, and reflect on the implications of our analysis for understanding experiences of genetic cancer risk.